Danger signal-dependent activation of human dendritic cells by plasma-derived factor VIII products - Miller, Lilija; Weissmüller, Sabrina; Ringler, Eva; Crauwels, Peter; van Zandbergen, Ger; Seitz, Rainer; Waibler, Zoe; the ABIRISK consortium; on behalf of (Thrombosis and Haemostasis, 2015)
Treatment of haemophilia A by infusions of the clotting factor VIII (FVIII) results in the development of inhibitors/anti-drug antibodies in up to 25 % of patients. Mechanisms leading to immunogenicity of FVIII products are not yet fully understood. Amongst other factors, danger signals as elicited upon infection or surgery have been proposed to play a role. In the present study, we focused on effects of danger signals on maturation and activation of dendritic cells (DC) in the context of FVIII application. Human monocyte-derived DC were treated with FVIII alone, with a danger signal alone or a combination of both. By testing more than 60 different healthy donors, we show that FVIII and the bacterial danger signal lipopolysaccharide synergise in increasing DC activation, as characterised by increased expression of co-stimulatory molecules and secretion of pro-inflammatory cytokines. The degree and frequency of this synergistic activation correlate with CD86 expression levels on immature DC prior to stimulation. In our assay system, plasma-derived but not recombinant FVIII products activate human DC in a danger signal-dependent manner. Further tested danger signals, such as R848 also induced DC activation in combination with FVIII, albeit not in every tested donor. In our hands, human DC but not human B cells or macrophages could be activated by FVIII in a danger signal-dependent manner. Our results suggest that immunogenicity of FVIII is a result of multiple factors including the presence of danger, predisposition of the patient, and the choice of a FVIII product for treatment.
Keywords: Haemophilia A; inhibitors; danger signals; dendritic cells; early immune responses